Korelasi Jurusan dan Asal Sekolah Terhadap Kemampuan Calon Guru Sekolah Dasar dalam Membedakan Rangkaian Seri dan Paralel - Muhammad Erfan; Mohammad Archi Maulyda; Arif Widodo; Vivi Rachmatul Hidayati; Tursina Ratu (Universitas PGRI Semarang, 2020)
The ability to distinguish series and parallel circuits is one of the core abilities that must be mastered before learning various electrical circuits, from simple electrical circuits to complex electrical circuits taught to students at the elementary school to secondary school level. Therefore, this study aims to determine whether there is a significant relationship between student majors during high school and the origin of schools on the ability of students to distinguish series and parallel circuits. This research is quantitative research with an ex-post-facto approach and conducted on students at the University of Mataram Elementary School Teacher Education Study Program with a proportion of 119 respondents (Science Major), 61 people (Social Science Major), 6 people (Language Major) and 7 respondents coming from vocational high schools. Data is collected using test techniques provided through Google Form. Data were analysed using the biserial point correlation. The hypothesis is tested by comparing the value of the biserial point correlation with the value of r product moment. The results showed that the biserial point value between Science Major - Social Science Major, Science Major – Language Major, Social Science Major – Language Major and Senior High School - Vocational School were all below the r product moment value so it can be concluded that there was no significant relationship between the majors of students during high school and the origin of the school's ability to distinguish series and parallel circuits.